Clean and Healthy Living Behaviour in Primary School - Ibrahim, Ikhsan; Hasanah, Nur; Hasibuan, Humaira Luthfia Putri; Lestari, Anggi Ayu; Adina, Nurul; Batubara, Inggrid Mentari; Siregar, Putra Apriadi; Taufiq, Ahmad (Pena Cendekia Insani, 2023)
As a result of their learning, students, teachers, and the school community practice clean and healthy living habits in the school. Problems that arise in primary schools show that students do not practice clean and healthy behaviours, such as rarely washing hands with running water and soap, rarely using healthy latrines, and rarely throwing garbage in its place, and that there are several cases of incidents such as diarrhoea, worms, typhoid, and ulcers. This study aims to identify the characteristics of clean and healthy behaviours in students at 5 Pancur Batu Primary School. Data collection techniques were carried out by distributing questionnaires on questions regarding healthy living behaviour and general questions covering health problems. The percentage of the indicator of healthy snack consumption in the school canteen has reached 81%. The percentage of indicators using clean and healthy latrines was as much as 78.6%. The percentage on the Regular and Measured Exercise indicator, obtained as much as 93.3%, looks almost perfect. Furthermore, 87.1% of the last indicator, eradicating mosquito flicks, was obtained. The percentage of students of Pancur Batu Primary School who have carried out clean and healthy living behaviour is 66.4%. Clean and Healthy Lifestyle education can increase knowledge about how to live a healthy life in the school environment so that students and students avoid disease. Increasing the knowledge and skills of students was carried out using lecture and demonstration methods. Because of the gallon sink, Pancur Batu primary School students can wash their hands before and after eating to avoid disease. Students also learned about personal hygiene, which is important for health.